The image of the marital migrants (As marital migrant’s example) - Ем, Н. Б.,; Aбейбековa, Г. (Journal of Oriental Studies, 2018)
The author research the reasons and conditions of perception of marital migrants in South Korean society. The author showed the basic postulates which television program of governmental Mass Media try to deliver to society. The image cultivated by TV programs telecast on the governmental level as the author supposes does not reflect the situation in relation to marriage migrants in South Korea. In spite incongruity of the fact of the uprising of some marital migrant sin the society, there is a real problem with the real situation of marital migrants.